Allograft outcomes of treated children with kidney transplant who developed plasma cell‐rich acute rejection (PCAR): A single center's experience. (22nd August 2019) - Alhamoud, Issa; Huang, Rong; Lacelle, Chantale; Burguete, Daniel; Hendricks, Allen R.; Torrealba, Jose R.; Seikaly, Mouin G.
Abstract: Introduction: PCAR is a rare form of ACR that may compromise renal allografts. This review evaluates the outcomes of a protocol used to treat PCAR (Study group), and compares these outcomes with a matched cohort with ACR (Control group). Methods: A retrospective analysis of 138 of pRTRs who underwent renal allograft biopsies between January 2008 and November 2016. Results: Seven biopsies revealed in situ hybridization of EBER‐negative PCAR (5%). Three Study group pRTRs lost their grafts within 3 months after rejection (43%). None of the Control group pRTRs lost their graft during this period. At the time of rejection, eGFR was different between the Control and Study groups (27.0 ± 19.9 mL/min per m 2 vs 40.0 ± 10.6 mL/min/1.73 m 2, respectively; P < 0.05). Among Study group pRTRs with functioning allografts (n = 4), treatment resulted in an increase in eGFR from nadir levels (27.0 ± 19.9 vs 55.6 ± 18.3 mL/min/1.73 m 2, P < 0.05). In the Study group, complications included neutropenia, BK and EBV viremia, and infusion‐related hypotension and hypertension. Summary: (a) Graft loss in Study group while remaining high (43%) was lower than that reported in the published pediatric literature. (b) Our protocol was associated with improvement in eGFR in all surviving pRTRs within the Study group. (c) No life‐threatening complications or malignancy were reported during the observation period.